Phosphorus speciation and bioavailability of sewage sludge derived biochar amended with CaO. (15th March 2019) - Liu, Qiang; Fang, Zheng; Liu, Yuan; Liu, Yangyang; Xu, Yunfeng; Ruan, Xiuxiu; Zhang, Xiaolei; Cao, Weimin
Highlights: CaO promote NAIP transformation to AP in SS derived biochar. Pyrolysis temperature also exert important effect on P speciation. CaO inhibit the loss of P and stabilize HMs in biochar. CaO amended biochar promote the growth of plants. Abstract: In this study, biochar samples were prepared from the co-pyrolysis of sewage sludge (SS) and CaO to explore the transformation of P speciation in sample. The potential of these biochar as a fertilizer to promote the growth of the plant was also evaluated. The result indicated that CaO addition can greatly facilitate the conversion of non-apatite inorganic phosphorus (NAIP) to apatite inorganic phosphorus (AP, mainly Ca3 (PO4 )2 and Ca3 Mg3 (PO4 )4 ). The addition of 10% CaO in feedstock is sufficient to convert SS inherent P into more bioavailable AP. Under such a dosage, AP content in biochar increased by 21.2–33.6% in contrast to CaO free sample at pyrolysis temperature of 500–800 °C, and water-soluble phosphorus (WSP) content decreased to less than 1% of TP. The addition of CaO can also apparently reduce Zn, Mn leaching from biochar. Additionally, hydroponics assay showed that CaO amended SS biochar can promote the growth of rice seedling. The results of this study indicate that preparing CaO amended SS biochar is a technically feasible strategy to utilize P resource in SS.